DYNAMIC PROCESSES ANALYSIS IN HIGH-SPEED SPINDLE ASSEMBLIES OF MACHINES TOOL WITH ACCOUNT DIFFERENT TYPES NONLINEARITY - STEPCHYN, YAROSLAV; OTAMANSKYI, VALENTYN; MALYSHEV, ILLIA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The productivity and accuracy machine parts often depend on the dynamic processes during machine and cutting operation. The increase requirements for machining operation and quality machine parts leads to the need to evaluate and take into account all the capabilities of the technological processing system (TS) to ensure the stability of the cutting process and increase speed. One of the features emergence and existence of self-oscillating processes, the least studied and dangerous in terms of the effect on sustainability ТS is the nonlinearity parameters elastic system of the machine tool and the processes occurring during cutting operation. Therefore, to assess the conditions for implementation of the cutting process with a steady limited amplitude of oscillations, it is necessary to analyze and take into account the main nonlinearities dynamics of the TS. The article considers dynamic processes in high-speed processing systems on the example of high-precision spindle assemblies, with analysis and following review of their different types nonlinearity. The machine tool spindle unit for the case of high-speed processing according to the working conditions approaches the scheme of the rotor system which self-oscillations can be caused by the action of non-conservative circulation-type forces that are not associated with external periodic loads or any resonant relationships: internal friction forces, hydrodynamic forces in sliding bearings and seals, electrodynamic and electromagnetic forces in the electrical components of motor-spindles. It is shown that if the nonlinearity is associated only with internal external friction and coefficients of friction forces do not depend on frequency, the amplitude and frequency of self-oscillations (unlike linear system) will depend only on relationship of friction forces.